The importance of banks, the quality of credit and the international financial order: reflections on the present crisis in South East Asia - DOW, C. (PSL Quarterly Review, 2013)
This essay considers the present financial crisis in South Asia, and how the international system might be better protected from the recurrence of such crises. It argues that, as with all major events, there were many causes. The essay focusses on the general tendency for bank lending to be unstable, which it argues was an underlying condition fro the crisis. The instability constitutes a problem for central banks, banks and their supervisors, both in borrowing countries, and also in lending countries. The essay suggests a number of ways in which international instability might be mitigated. This instability is an aspect of the problem faced by all countries of avoiding over-speculative conditions in domestic financial markets in order to mitigate fluctuations and preserve stable growth. JEL Codes: G15, F34, D02